Surpassing the conventional heisenberg limit using classical resources - Jin, X; Lebrat, M; Zhang, L; Lee, K; Bartley, T; Barbieri, M; Nunn, J; Datta, A; Walmsley, I (2013)
We report the experimental estimation of the Kerr coefficient of an optical fiber. Using bright classical fields and shot-noise-limited detection, we show the precision scaling of 1=N3=2 in a room-temperature, all-optical system. © 2013 Optical Society of America.